Upgrading a legacy manufacturing cell to IoT - Cunha, João (2022)
Many industries, like aeronauting construction are still equipped with legacy machines and are not keen to change old, however fully functional, equipment to new ones. Hence, an upgrade must be found to cope the legacy and fully functional machines to IOT technologies. This paper is a contribution to embrace those challenges in a new IoT architecture able to support the creation of solutions for Smart Industries. Internet of Things is increasing acceptance and the infrastructure for them is becoming available. This leads to an insurgence on investments and development of new dedicated IoT infrastructures. Industries need to adapt quickly to this constant technological evolution, implementing measures and connecting machines and robots at critical points to the Internet, instrumenting them using the concept of IoT, with the major goal of implementing a flexible, secure, easy to maintain and capable to evolve infrastructure, when legacy equipment is involved. The availability of machines and other critical assets directly affects the effectiveness of manufacturing operations. The architecture design offers security, flexibility, simplicity of implementation and maintenance, and is resilient to failures or attacks and technologically independent. Field tests are reported to evaluate key aspects of the proposed architecture.